2019
DOI: 10.14743/apem2019.2.325
|View full text |Cite
|
Sign up to set email alerts
|

The investment strategy and capacity portfolio optimization in the supply chain with spillover effect based on artificial fish swarm algorithm

Abstract: Spillover effect can lead to the free-riding behavior when joint investment takes place in the supply chain. This study examined the investment strategies of two competitive retailers who considered whether to invest a shared contract manufacturer (CM) or not. The supply chain members' operational decisions in four scenarios were analyzed through a Cournot competition model, and the paths of the retailers' investment strategies were examined. The CM's capacity portfolio optimization was NP-hard in nature, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In this course, Mittelstaedt [29] and Chiou et al [30] found that free-riding behavior weakens the enthusiasm of service retailers. Zheng and Bao [31] established a Cournot game competition model, including one manufacturer and two retailers producing alternative products, to study the business decision-making of each member. They found that the joint investment intention of the two retailers decreased with the increase in the free-riding coefficient caused by the product spillover effect.…”
Section: Negative Impact Of Free-riding Behaviormentioning
confidence: 99%
“…In this course, Mittelstaedt [29] and Chiou et al [30] found that free-riding behavior weakens the enthusiasm of service retailers. Zheng and Bao [31] established a Cournot game competition model, including one manufacturer and two retailers producing alternative products, to study the business decision-making of each member. They found that the joint investment intention of the two retailers decreased with the increase in the free-riding coefficient caused by the product spillover effect.…”
Section: Negative Impact Of Free-riding Behaviormentioning
confidence: 99%